A retinal hyperspectral imaging biomarker for Alzheimer's disease: Preliminary study of the influence of eye diseases on imaging scores: Biomarkers (non‐neuroimaging) / novel biomarkers. (7th December 2020) - van Wijngaarden, Peter; Hui, Flora; Dang, Darvy; Ha, Jason; Fowler, Christopher J; Villemagne, Victor LL; Rowe, Christopher C; Masters, Colin L; Williamson, Robert; Crowston, Jonathan G; Hadoux, Xavier
Abstract: Background: We and others have demonstrated that in vivo retinal hyperspectral imaging may serve as a non‐invasive biomarker of brain amyloid beta (Aβ) levels (Hadoux, 2019; More, 2019). We next sought to determine whether individuals with a range of common eye diseases have imaging scores distinct from those of people known to have high Aβ burden on brain PET imaging. Method: Retinal hyperspectral imaging was performed on people presenting to ophthalmology outpatient clinics with visually significant cataracts (n=10), glaucoma (n=18) or diabetic retinopathy (n=14). Hyperspectral imaging scores were calculated for each participant using image processing methods described previously (Hadoux, 2019). Scores were compared with those of participants with high Aβ burden on brain PET imaging (n=15) and age‐matched PET‐negative controls (n = 20) (Hadoux, 2019). Result: Participants in each group were similar for gender and age. Significant differences in hyperspectral imaging scores were found between PET+ participants and all other groups (Figure 1). Post‐hoc analysis demonstrated that PET‐ control participants had lower hyperspectral imaging scores than PET+ participants with normal (≥24, n=7; p=0.01) or reduced (<24, n=8; p=0.035) MMSE scores. Conclusion: We have shown that individuals presenting to outpatient ophthalmology clinics with a range of eye diseases including cataract, diabetic retinopathy and glaucoma have retinal hyperspectral imaging scores that are distinct from those of individuals with high Aβ burden on brain PET imaging. Further studies are warranted to establish the influence these eye diseases on hyperspectral imaging scores in PET+ individuals. We also provide evidence that retinal hyperspectral scores may be elevated in PET+ individuals with normal MMSE scores, indicating that the method may have a role in identifying those with pre‐symptomatic Alzheimer's disease. Prospective studies are underway to test this hypothesis. References: Hadoux, X, et al. Nature Communications; 2019; More, SS, et al. ACS Chem Neurosci. 2019.